An online database of nuclear electromagnetic moments - Mertzimekis, T. J.; K. Stamou; A. Psaltis (Nucl. Instrum. Meth. Phys. Res. A, 2016)
Abstract Measurements of nuclear magnetic dipole and electric quadrupole moments are considered quite important for the understanding of nuclear structure both near and far from the valley of stability. The recent advent of radioactive beams has resulted in a plethora of new, continuously flowing, experimental data on nuclear structure – including nuclear moments – which hinders the information management. A new, dedicated, public and user friendly online database (http://magneticmoments.info) has been created comprising experimental data of nuclear electromagnetic moments. The present database supersedes existing printed compilations, including also non-evaluated series of data and relevant meta-data, while putting strong emphasis on bimonthly updates. The scope, features and extensions of the database are reported.
Keywords: Nuclear data